Gaya Bahasa Dalam Lirik Lagu Bergenre Indie - Rosmalizah Rasyid; Yulliani Rachmawati (Simpati, 2023)
This article aims to find out the style of language used in the lyrics of indie genre songs, a genre that is much liked by the general public from the age of teens to the age of over 50 years. This indie genre song is liked by many people because the language used is pleasant to hear and friendly to the ear because the language used is very upholding Indonesian especially the use of Indonesian is a good and correct standard Indonesian that is rarely used at this time, because at this time the majority of millennial generation children are also generation Z children who at this time in speaking often use slang, namely Indonesian mixed with English